Perlindungan Hukum Rahasia Dagang dan Hak Paten Produk dalam Kontrak Kolaboratif Rantai Pasok Hulu-Hilir - Chandra Erick Manaek Pandapotan Lumban Gaol; Etty Mulyati; Christianto Tonggo Arisepebra Sigalingging (Jurnal Interpretasi Hukum, 2025)
Collaboration in upstream-downstream supply chains is crucial for efficiency and innovation, yet it involves the exchange of valuable trade secrets and patented technologies. Although Indonesia's Intellectual Property Rights (IPR) legal framework exists, literature often lacks integration of simultaneous protection for Trade Secrets and Patents within the complexity of collaborative supply chain contracts, creating a gap between legal theory and the practical need for intellectual asset protection in business collaborations. This study aims to analyze how Indonesian positive law can serve as a foundation and how contracts can be designed as the primary instrument to provide optimal simultaneous legal protection for Trade Secrets and Patent Rights within the context of collaborative upstream-downstream supply chain agreements. It employs a normative legal research method with statutory, conceptual, and analytical approaches towards the Trade Secret Law, the Patent Law as amended by the Job Creation Law, the Civil Code, and secondary legal materials. Key findings indicate that effective protection requires a combination of proactive efforts by IPR owners (maintaining confidentiality, registering patents) and precise contract drafting, encompassing specific clauses regarding IPR definitions, confidentiality, licensing, ownership of joint inventions, and dispute resolution. The results affirm that the synergy between compliance with formal IPR regimes and meticulous drafting of collaborative contracts is a vital strategy for managing risks and protecting intellectual assets, serving as a risk management tool, clarifying expectations, and providing an additional legal basis within Indonesian supply chains.